1999
DOI: 10.1016/s1010-7940(99)00078-0
|View full text |Cite
|
Sign up to set email alerts
|

Bilateral lung transplantation via two sequential anterolateral thoracotomies1

Abstract: The bilateral sequential anterolateral thoracotomy represents a safe and minimal invasive approach for BLTX compared with the clam shell incision. It minimizes the operative trauma, improves postoperative functional recovery and prevents the potential spread of unilateral complications to the other pleural cavity.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
7
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
5
4
1

Relationship

0
10

Authors

Journals

citations
Cited by 15 publications
(7 citation statements)
references
References 5 publications
0
7
0
Order By: Relevance
“…Bilateral lung transplants are performed as sequential single-lung transplants via a clamshell incision or bilateral anterolateral thoracotomies if preferred and technically feasible (Taghavi et al 1999). The sequential transplant strategy not only allows for the avoidance of CPB in most (60% -75%) cases, but also avoids a tracheal anastomosis, which was used in the original en bloc double-lung transplant operation ).…”
Section: Surgical Techniquementioning
confidence: 99%
“…Bilateral lung transplants are performed as sequential single-lung transplants via a clamshell incision or bilateral anterolateral thoracotomies if preferred and technically feasible (Taghavi et al 1999). The sequential transplant strategy not only allows for the avoidance of CPB in most (60% -75%) cases, but also avoids a tracheal anastomosis, which was used in the original en bloc double-lung transplant operation ).…”
Section: Surgical Techniquementioning
confidence: 99%
“…It has been suggested that the CS approach may contribute to postoperative complications by inducing surgical inflammation, postoperative pain with respiratory compromise and potential for impaired wound healing. To overcome these difficulties, a minimally invasive lung transplantation (MILT) approach, which avoids both the clamshell incision and the routine use of CPB, has been advocated recently [10][11][12][13][14]. Although these centres have achieved good clinical and cosmetic results when compared with historical data, there is limited information comparing the minimally invasive approach and the clamshell method in a simultaneous fashion.…”
Section: Introductionmentioning
confidence: 99%
“…At the early onset of bronchus sleeve resections, the vast majority of thoracic surgeons favored a posterolateral access for bronchial reconstructions due to the excellent exposition of the carinal area and to adequate space for surgical maneuvers (4). Because of the severe soft tissue trauma and respectable rib spreading required for this access and by the process of gaining experience with bronchial reconstruction, the anterolateral thoracotomy and the anterior hilum preparation became also commonly favorable for most surgeons for sleeve procedures (5,6). Parallel to the above surgical evolution, techniques of video assisted thoracoscopic surgery were widely adopted and anatomical resections for small, peripherally located tumors became also standard in high volume thoracic centers (7)(8)(9)(10).…”
Section: Introductionmentioning
confidence: 99%